2020
DOI: 10.3390/rs12030408
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos—Cement Roofing Identification Using Remote Sensing and Convolutional Neural Networks (CNNs)

Abstract: Due to the pathogenic nature of asbestos, a statutory ban on asbestos-containing products has been in place in Poland since 1997. In order to protect human health and the environment, it is crucial to estimate the quantity of asbestos–cement products in use. It has been evaluated that about 90% of them are roof coverings. Different methods are used to estimate the amount of asbestos–cement products, such as the use of indicators, field inventory, remote sensing data, and multi- and hyperspectral images; the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Given that no digital pre-demolition audit dataset exists in Sweden, nor can building material records be found in the national building registers, the study proposed an innovative data coupling method by adding environmental inventories from the field study to the building information database from authorities. A similar data coupling approach has been performed by Wilk et al [20] and Krówczyńska et al [21] to study the spatial distribution of asbestos-cement roofing. To assess the potential of using environmental inventories for hazardous materials identification, a training dataset consisting of pre-demolition audits from demolished and renovated buildings in the City of Gothenburg constructed earlier than 1982 and national building registers at a regional scale was created.…”
Section: Methodsmentioning
confidence: 96%
“…Given that no digital pre-demolition audit dataset exists in Sweden, nor can building material records be found in the national building registers, the study proposed an innovative data coupling method by adding environmental inventories from the field study to the building information database from authorities. A similar data coupling approach has been performed by Wilk et al [20] and Krówczyńska et al [21] to study the spatial distribution of asbestos-cement roofing. To assess the potential of using environmental inventories for hazardous materials identification, a training dataset consisting of pre-demolition audits from demolished and renovated buildings in the City of Gothenburg constructed earlier than 1982 and national building registers at a regional scale was created.…”
Section: Methodsmentioning
confidence: 96%
“…It was pointed out that similar studies are needed in other countries to estimate the ongoing environmental and occupational MM risks worldwide, including the contribution of chrysotile. The possible solution to gauge the asbestos environmental exposure would be to estimate the geographical distribution of asbestos products still in use (Krówczyńska et al, 2020).…”
Section: Articlementioning
confidence: 99%
“…The macro-level involves detection and estimation of regional ACMs via image recognition in remote sensing. By compiling the aerial photographs, hyperspectral data, and multispectral imagery, Krówczyńska et al [13] built a hybrid database for modeling the quantity and location of asbestos-cement roofing. In their findings, the convolutional neural networks exhibited an overall high accuracy in classifying nature color images and color-infrared imagery of asbestos-cement roofing from other roof materials.…”
Section: Machine Learning In Hazardous Materials Identificationmentioning
confidence: 99%
“…With the improved data availability and the demand for decontamination in buildings, researchers started to adopt machine learning techniques to streamline the traditional modeling process and enhance the hazardous material recognition rates. Pilot studies showed promising results in estimating the amount and the spatial distribution of insitu hazardous materials [9,13] and facilitating semi-automated material sorting [14,15] by adopting machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%